Anti-inflammatory effects of total saponins of Panax notoginseng - Li Shu-hui; Chu Yan (Acta Pharmacologica Sinica, 2016)
AIM: To study the anti-inflammatory effects of total saponins of Panax notoginseng (PnS). METHODS: Rat air-pouch acute inflammatory model was established with s.c. carrageenan (Car, 25 mg.kg-1). The protein content in exudate was measured. Micro-acid titration assay and radioimmunoassay (RIA) were applied respectively to investigate effects of PnS on phospholipase A2 (PLA2) activity and dinoprostone (Din) content in exudate. Fura-2 fluorescence technique was used to determine the intracellular free calcium concentration in neutrophils (Neu-[Ca2+]i). RESULTS: At 12 h, PnS 60-240 mg.kg-1 i.p. reduced Neu counts, protein content [(7.7 +/- 1.3) to (4.4 +/- 1.4) g.L-1], and Din content [(1619 +/- 391) to (883 +/- 268) ng.L-1]; inhibited the PLA2 activity in exudate [(248 +/- 42) to (157 +/- 35) kU.L-1] in a dose-dependent manner. PnS 60, 120, and 240 mg.kg-1 lowered the level of Neu-[Ca2+]i with the inhibitory rate of 9.1%, 33.2%, and 39.4%, respectively. CONCLUSION: PnS has an obvious anti-inflammatory effect and its mechanisms are related to the inhibition of the Neu-[Ca2+]i level and PLA2 activity, and reduction of Din content.